Advances in Etiology of High Incidence of Thyroid Cancer in Women - TAN Meijuan; YANG Shijie; LIU Zhenzuan; LIU Yumeng; XU Xiequn (Xiehe Yixue Zazhi)
Thyroid cancer is the only non reproductive tumor that mainly occurs in women. The morbidity rate of female thyroid cancer is three times higher than that of male thyroid cancer. However, the existing studies have not systematically summarized the factors that contribute to the high incidence of thyroid cancer in women. This paper reviews all the literatures that mention the high incidence of thyroid cancer in women, and sorts out the main reasons, such as estrogen, obesity, reproductive factors, oxidation antioxidant system imbalance, X chromosome, etc., which are the main reasons for the current research finding that the incidence rate of thyroid cancer in women is higher than that in men. This paper makes a vivid graphic analysis and summary of the reasons, providing a research direction for future researchers to research on gender duality of thyroid cancer, and providing a certain reference for the clinical diagnosis and treatment of gender differences in thyroid cancer.